Federated States of Micronesia : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that the economic activity in the Federated States of Micronesia (FSM) is estimated to have slowed. Despite the use of the bump-up funds by some of the FSM's four state governments to boost spending during FY2002, GDP is estimated to have grown only by 0.8 percent. The fiscal stimulus appears to have been mostly offset by an emerging fiscal crisis in Chuuk and a 'wait and see' attitude of the private sector in the face of uncertainty associated with the new Compact of Free Association.